Legal Protection for Taxpayers Participants of Voluntary Disclosure Program in the Law on Harmonization of Tax Regulations - Subagyo, Achmad; Abdullah, Saiful; Saleh, Moh (jfpublisher, 2022)
The tax laws and regulations have changed many times, but these changes have not had a strong impact in terms of fulfilling the tax function as a regulator and source of financing for state administration and national development, especially during this Covid-19 pandemic. Therefore, the government regulates and changes several provisions in the field of taxation, such as Law No. 11/2020 concerning job creation and Law No. 7 concerning HPP (Harmonization of Tax Regulations). Minister of Finance stated that the HPP Law would provide provisions for the government to overcome disruption or shock of Covid-19 after effect. The objectives of this research are to describe the analysis of asset arrangements that must be reported in the Voluntary Disclosure Program and analyze legal remedies that can be taken by taxpayers who experienced losses as participants. This research used a normative type of research. The approach used in this research is a descriptive analysis. The source data of this research consist of primary and secondary legal materials. In addition, the data collection used library research. Taxpayers participating in the Voluntary Disclosure Program can take legal action against all disputes related to the Tax Amnesty Program through an Objection Application when the Taxpayer receives an SKPKB (Tax Underpayment Assessment Letter). Meanwhile, based on the decision of the Director General of Taxes, apart from the issuance of SKPKB, it can only be resolved through a lawsuit to the Tax Court.